The Study On Microencapsulation Of Vanilla Extract - Dwi Setyaningsih; Reni Rahmalia; . Sugiyono (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Natural vanilla extract microencapsulation was done by spray drying method, using maltodextrin DE10 and modified cassava starch (Flomax 8) as coating material. Selection of coating material ratio of maltodextrin DE10 : Flomax8 (1:0, 1:1, 0:1, 1:2, 2:1) was done as pre-treatment, resulted in an optimum ratio of 2:1. Three different treatments were applied: type of coating material (maltodextrin DE10, and maltodextrin DE10: Flomax8 = 2:1), coating material concentration (10, 20, and 30%) and vanilla extract - coating material ratio (3:2, 2:1 and 3:1). Type of coating material, coating concentration and ratio between vanilla extract and coating material gave a significant difference to the yield, vanillin content and vanillin recovery. Vanillin extract coated by maltodextrin DE10:Flomax8 2:1 gave yield, vanillin content and vanillin recovery higher than only maltodextrin. The highest vanillin content and vanillin recovery obtained from 30% concentration of coating material. The higher ratio of vanillin extract to coating material gave the higher vanillin content, but recovery was lower. The type of coating material gave a significant effect to the solubility of vanilla powder. The concentration of coating material and ratio between extract vanilla and coating material did not affect the solubility. The type of coating materials, coating material concentration and ratio between vanilla extract and coating material did not affect water activity of the obtained vanilla powder.